Dampak Penanaman Pohon Hutan di Lahan Perkebunan Karet (Hevea brasiliensis Muell.Arg) Pada Sifat Biologi Tanah di Kecamatan Bahorok Kabupaten Langkat - Muhammad Thamrin; Abdul Rauf; Benny Hidayat (Jurnal Agroekoteknologi, 2017)
ABSTRACT The objectives of the research ware to study the effect of Gaharu, Damar, and Meranti wood planting on rubber plantation site over soil biological properties in District Bohorok Langkat as well as to see the effect of the best tree for land space in rubber plantation. Research conducted at Land of Rubber Plantation in the village of Batu Jonjong and Timbang Lawan in February 2016 until June 2016. This research used survey descriptive method by purposive sampling method. Sampling chosen ware for: control as rubber without intercrops (K0), rubber trees intercrops with Gaharu (K1), rubber trees intercrops with Damar (K2) and rubber trees intercrops with Meranti (K3). The measured parameters ware organic C, total N, C/N, microbes total, soil respiration, soil macrofauna and earthworms. The results showed that planting gaharu, damar and meranti gave effect improvement of biological properties in rubber plantation and the best tree for land space in rubber plantation was rubber with Damar trees (K2). Keywords: Plant-stream, purposive sampling, soil biology